PENGARUH AKUNTANBILITAS, TRANSPARASI DAN PARTISIPASI MASYARAKAT TERHADAP PEMBERDAYAAN MASYARAKAT DI DESA KARANGLO KECAMATAN GODEAN - Pramudi, Alifa Ilham; As’ari, Hasim (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
Village funds, which are a source of income for each village, need to be controlled over their management so that they are right on target and can improve the standard of living of the community. This study aims to determine the effect of Accountability, Transparency, and Community Participation on Community Empowerment in the Management of Village Funds in Karanglo Village, Godean District. Respondents of this study were Village Officials and family heads of the Karanglo Village community, Godean Subdistrict so the results of the sample selection used as the object of research (sample) were 47 respondents. This type of research is quantitative. Data collection methods using survey techniques with questionnaires determining the sample using the Slovin method and purposive sampling. Regression analysis method. The results showed that the variables of accountability, transparency, and community participation had a positive and significant effect on community empowerment. Key words: village funds, accountability, transparency, community participation.